Fingertip tactile sensation via piezoelectric micromachined ultrasonic transducers with an amplified interface - Sone, Junji (Scientific reports, 2024)
Tactile devices are often used in the field of robotics; however, the development of compact high-resolution tactile devices remains challenging. In this study, we developed a haptic device for force presentation using a DC motor and a tactile sensation device to simultaneously present haptic and tactile stimuli. A microelectromechanical system was selected to maintain the compactness of the tactile device. Piezoelectric micromachined ultrasonic transducers are known for high-power stimulation, and we selected lanthanum-doped lead zirconate titanate as the high-power amplified actuator. A finger mount structure that transfers force for amplifying ultrasonic waves was considered to combine acoustic pressure and aeroacoustics by attaching silicone rubber. The device was fabricated, and the performance of the tactile sensations was evaluated. The developed device uses the novel concept of combining acoustic pressure and aeroacoustics, and its compactness renders it suitable for wearable systems.